Answer:
f(x) = 6x³ - 17x² + 11x - 2
Explanation:
Given the zeros x = 2, x =
, x =
then the factors ar
(x - 2), (x -
), (x -
)
By equating the fractional factors to zero we can express them as integer factors, that is
x -
= 0 ( multiply through by 3 )
3x - 1 = 0
x -
= 0 ( multiply through by 2 )
2x - 1 = 0
Thus the factors are (x - 2), (3x - 1), (2x - 1)
The polynomial is then the product of the factors.
f(x) = (x - 2)(3x - 1)(2x - 1) ← expand last 2 factors using FOIL
= (x - 2)(6x² - 5x + 1) ← distribute
= 6x³ - 5x² + x - 12x² + 10x - 2 ← collect like terms
f(x) = 6x³ - 17x² + 11x - 2 ← cubic polynomial